The quest for rights: ideal and normative dimensions - La Torre, Massimo; Niglia, Leone; Susi, Mart (Edward Elgar Publishing, 2019)
"In an era that seeks to challenge the notion of the universality of human rights, this thought-provoking book explores their fundamental nature and considers the work and influence of German legal scholar and constitutional lawyer Robert Alexy, on contemporary jurisprudence and European Union law. What is the justification of balancing versus trading off fundamental rights against other rights and collective goods? Are there utilitarian considerations that can limit the normative force of human rights? Utilising both "ideal" and "critical" perspectives, this innovative book focuses on those inevitable questions which lie at the heart of any contemporary human rights discourse, as the premise of the dual nature of law is developed. A corresponding 'normative' perspective seeks to investigate the broader legal domains of the topic. This analytical book will be a key resource for students and scholars working in the fields of jurisprudence and legal theory, history and philosophy of law and comparative and EU law alike"--